Towards pluralistic legal minds : pedagogical theories underpinning teaching of comparative legal research methodology - Malik, Hanna Maria; Cadillo Chandler, Dhanay (Taylor & Francis, 2026)
This paper shares our experience of research-based teaching of comparative law. Our main teaching goal is to provide a deep approach to learning and by extension enhance critical thinking about law as a social and political phenomenon using comparative research as a tool of legal learning. To achieve this, it is of paramount importance to push legal thinking beyond traditional legal dogmatics and broaden epistemic understanding of how scientific and legal knowledge is created and developed. Thus, our teaching content highlights the entire intellectual spectrum of comparative law emphasising the critical and postmodern approaches based on pluralist thinking. Thereafter, the students get to experience existent diversity in legal thinking. On the other hand, shifting away from traditional comparative legal research methods poses a difficulty both for students accustomed to traditional methods of legal reasoning, and for teachers – us – when passing on the knowledge. This challenge may derive from the fact that existent comparative law literature focuses on the theoretical underpinings that become highly sophisticated and intricate to implement, rather than providing tools on how to implement and teach the methodology.